Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients - Hack, Carolin; Häberle, Lothar; Geisler, K.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Fasching, Peter; Uder, Michael; Wachter, David; Jud, Sebastian; Löhberg, Christian; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node metastases in patients with primary breast cancer. Methods: In this retrospective study we analyzed primary, metastasis-free breast cancer patients from one breast center for whom data on MD and staging information were available. A total of 1831 patients were included into this study. MD was assessed as percentage MD (PMD) using a semiautomated method and two readers for every patient. Multiple logistic regression analyses with nodal status as outcome were used to investigate the predictive value of PMD in addition to age, tumor size, Ki-67, estrogen receptor (ER), progesterone receptor (PR), grading, histology, and multi-focality. Results: Multifocality, tumor size, Ki-67 and grading were relevant predictors for nodal status. Adding PMD to a prediction model which included these factors did not significantly improve the prediction of nodal status (p = 0.24, likelihood ratio test). Conclusion: Nodal status could be predicted quite well with the factors multifocality, tumor size, Ki-67 and grading. PMD does not seem to play a role in the lymphatic spread of tumor cells. It could be concluded that the amount of extracellular matrix and stromal cell content of the breast which is reflected by MD does not influence the probability of malignant breast cells spreading from the primary tumor to the lymph nodes. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast cancer; estrogen receptor; Ki-67; mammographic density; nodal status; progesterone receptor